Some General Manifestations of Transition Periods of International Relations System - Kocharyan, Shavarsh (YSU Journal of International Affairs, 2024)
During the period of operation of the international relations system (IRS), the main actors of international relations (superpowers) that formed that system, despite the deep contradictions that exist among themselves, have a common interest in maintaining the current system, because it provides them with a privileged position in world politics. Guided by this common interest, the superpowers restrain each other and, with joint efforts, restrain actions of other actors in international relations that could undermine the existing system.During the transition period of the IRS, on the one hand, the deterrence mechanism ceases to function, and on the other hand, the superpowers seek to use or provoke processes that will strengthen themselves and weaken the positions of their opponents in the struggle for the new IRS. The expression of the transformation of the interests of the superpowers are the general manifestations of the transition periods of the IRS 1 - an increase in the number of local and regional armed conflicts and their intensity; 2 - increase of genocide and other crimes against humanity; 3 - disregard of international law by actors of international relations and non-state organizations; 4 - discrediting of universal structures of international cooperation and decline in effectiveness of activities; 5 - a world war in which the victorious superpowers establish a new IRS. The listed manifestations, so far with the exception of the world war, are also characteristic of the current transitional period from Yalta-Potsdam to the new IRS.
Keywords: system of international relations; world politics; armed conflicts; genocide; crimes against humanity; international legal system; structures of international cooperation; interests of superpowers